Peningkatan Kemampuan Menulis Surat Lamaran Pekerjaan melalui Model Pembelajaran Think-Pair-Share pada Siswa Kelas XII MIA 1 SMA Negeri 1 Pancur Batu - Maria Simanjuntak (Medan Resource Center, 2021)
The purpose of this study was to determine how the ability to write job application letters for students of class XII MIA 1 SMA Negeri 1 Pancur Batu and to find out whether cooperative learning with the Think-Pair-Share model can improve the ability to write cover letters for students of class XII MIA 1 SMA Negeri 1 Pancur Batu. . The benefit of this research for students is to increase knowledge and insight in writing job application letters. The benefits of this research for teachers are: as an effort to offer new innovations in how to learn to write job application letters, as an effort to motivate students in writing job application letters, and as an effort to improve performance, abilities, and professionalism in improving the quality of learning in the classroom. The benefit of this research for researchers is to broaden knowledge and provide learning experiences that foster research abilities and skills as well as broader knowledge. This study uses classroom action research (action research) in two rounds (cycles). Each round consists of four stages, namely: planning, activities and observations, reflection, and revision. The target of this research is the students of class XII MIA 1 SMA Negeri 1 Pancur Batu. The data obtained in the form of subjective test results and observation sheets of teaching and learning activities.